2015
DOI: 10.7150/ijms.11988
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activity of Colistin in Combination with Tigecycline against Carbapenem-Resistant Acinetobacter baumannii Strains Isolated from Patients with Ventilator-Associated Pneumonia

Abstract: Objective: This study investigated the minimum inhibitory concentration (MIC) values and in vitro activity of colistin in combination with tigecycline against carbapenem-resistant Acinetobacter baumannii strains isolated from patients with ventilator-associated pneumonia (VAP) using the E-test method.Methods: A total of 40 A. baumannii strains, identified using the Phoenix Automated Microbiology System (Becton, Dickinson and Co., Franklin Lakes, NJ, USA) by conventional methods, were included in this study. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
2
7
0
2
Order By: Relevance
“…This suggests that the addition of tigecycline to colistin may be harmful, considering the removal of susceptible-range wells and poor clinical outcomes seen in patients who received that combination. Our study correlates with a study by Cikman and colleagues that demonstrated a high rate of antagonism with tigecycline-colistin against XDR A. baumannii (12). Taken together, the results show that utilizing drug combinations that inhibit growth in SAC wells may be a more appropriate alternative than utilizing a combination that does not when treating XDR A. baumannii pneumonia.…”
supporting
confidence: 77%
“…This suggests that the addition of tigecycline to colistin may be harmful, considering the removal of susceptible-range wells and poor clinical outcomes seen in patients who received that combination. Our study correlates with a study by Cikman and colleagues that demonstrated a high rate of antagonism with tigecycline-colistin against XDR A. baumannii (12). Taken together, the results show that utilizing drug combinations that inhibit growth in SAC wells may be a more appropriate alternative than utilizing a combination that does not when treating XDR A. baumannii pneumonia.…”
supporting
confidence: 77%
“…Tigecycline and colistin combination therapy has been shown to be antagonistic in Ac. baumannii , specifically at low concentrations in some studies (Albur et al ., ; Cikman et al ., ) but synergistic in others (particularly in Enterobacteriaceae) (Ku et al . ; Betts et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 There were no antagonistic effects in our findings. In contrast, Cikman et al 17 reported 80% antagonistic effects from a colistin/tigecycline combination in CRAB strains. This different outcome might be a result of the method used for synergy testing.…”
Section: Discussionmentioning
confidence: 90%
“…8,9,15,16 However, antagonistic effects of such a combination might be detected. 17 Since the benefit of a combination of colistin and tigecycline is ambiguous, we conducted this particular study to determine in vitro antimicrobial susceptibility and the synergistic activity of colistin in combination with tigecycline against clinical strains of CRAB.…”
mentioning
confidence: 99%